2005
DOI: 10.1016/j.rmed.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the costs of managing patients with chronic obstructive pulmonary disease

Abstract: The economic consequences of chronic obstructive pulmonary disease (COPD) are considerable, although the factors that best predict costs are largely unknown. This study used a population-based cohort to identify the clinical factors during an index year that were most predictive of increased direct medical costs in the subsequent year, and to develop a predictive model that described the cost variations in COPD. The medical records of 2116 patients enrolled in one regional health system who had COPD and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
2
39
0
2
Order By: Relevance
“…Mapel et al (27) Multiple analysis of factors most predictive of future direct medical costs in COPD, 2116 subjects…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…Mapel et al (27) Multiple analysis of factors most predictive of future direct medical costs in COPD, 2116 subjects…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…We have examined the validity of these codes and this system for identifying COPD by medical record abstraction in previous projects and found them to be accurate, with more than 95% of these patients having documented clinical evidence to support the diagnosis. 18 For inclusion in the algorithm development group, we also required that COPD patients had received their first COPD diagnosis (index diagnosis) between 1997 and 2001. To be considered a new diagnosis, there could be no diagnosis codes for COPD appearing prior to the index diagnosis dating back to the patient' s initial membership in the health plan, or as of January 1, 1990.…”
Section: Algorithm Development and Validation Cohortsmentioning
confidence: 99%
“…14,15 We have shown in our previous studies that COPD patients have a higher risk of having comorbid conditions such as heart disease and that they also have substantially increased health care costs related to these diseases. [16][17][18] If patterns of health care utilization characteristic of undiagnosed COPD can be identified, then it is possible that the information found in administrative data, such as demographic information, health care claims, and pharmacy records, could be used as an efficient means of identifying persons at risk.…”
mentioning
confidence: 99%
“…Three models specified COPD-related costs by age. Several studies investigated the association between age and COPD-related costs and found no significant impact of age on costs [43][44][45][46]. This may be because age and FEV1% predicted are correlated and in three of these studies FEV1% was also included in the multivariate model and found to be a significant predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in COPD is associated with age and FEV1, but also with co-morbidities, BMI, dyspnea and several other clinical parameters [32,34,36,38,53]. BMI also seems to be associated with quality of life in COPD [39,54] and co-morbidities may affect COPD-related costs [44,45,55,56]. Only the more recently developed models of Asukai (simulation) and Briggs included these types of clinical parameters and are therefore more suitable to evaluate personalized treatment that the other models .…”
Section: Discussionmentioning
confidence: 99%